Review buku I Want to Die But I Want to Eat Tteokpokki: Sebuah buku tentang kesehatan mental - Mutammima, Fadilah (Maliki Interdisciplinary Journal, 2023)
This book review aims to find out how important it is to maintain mental health and how mental health can greatly influence everyday life. This can influence the spirit of life, self-confidence, desire to do something, relationships with fellow humans both individually and in the environment. wider. The book I Want to Die But I Want to Eat Tteokpokki is a book written by Baek Se Hee, a South Korean writer, and is the story of his journey in searching for answers and treatment for the anxiety and depression he is experiencing. The anxiety and depression disorders that are experienced by Baek Se Hee also known as Distimia.